PENGARUH PENEMPATAN PRODUK DAN KESADARAN MEREK TERHADAP NIAT MEMBELI - Selly Juliana; Sabrina O. Sihombing (Jurnal Manajemen dan Pemasaran Jasa, 2019)
Zipping and zapping is better known as TV channel transfers that viewers can record, pause and repeat TV broadcasts. It can be stated that zipping and zapping can cause ads to be no longer effective and efficient as a means of promotion and communication of products. Therefore, to create good communication, advertising can be used and product placement is one of the advertising choices. Product placement is one of the most advanced advertising industries. Product placement makes the audience's attention indirectly focus on the brand or product that is placed on television shows or films, and companies that use product placement can avoid zipping and electric shocks. Based on the previous explanation, this research was conducted to determine whether product placement had a positive effect on brand awareness and intention to buy Indonesian people. This research was conducted with quantitative research methods through an online questionnaire. This study applied a purposive sampling method and was aimed at respondents who had watched Indonesian Idol 2018. The study consisted of 154 respondents. Data were analyzed using structural equation modeling. The results show that there are two supported hypotheses and one hypothesis that is not supported. This study concludes that there is a positive influence of product placement and brand awareness, there is no positive influence of product placement and purchase intention, and there is a positive influence of brand awareness and purchase intention.